Insects as a reservoir and possible vector for antimicrobial resistance in the environment - Falcus, Kirsty J. (2024)
Antimicrobial resistance (AMR) is a global health concern. The impact of AMR on the environment is compounded by antibiotic use in agriculture specifically livestock. Insects are prevalent around livestock and their faeces. Flies are commonly found on cattle farms and mealworms are a pest associated with poultry farming.